RETRACTED: Cancer-Associated Fibroblasts-Derived Exosomes Suppress Immune Cell Function in Breast Cancer via the miR-92/PD-L1 Pathway - Dou, Dongwei; Ren, Xiaoyang; Han, Mingli; Xu, Xiaodong; Ge, Xin; Gu, Yuanting; Wang, Xinxing (Frontiers in Immunology, 2020)
Cancer-associated fibroblasts (CAFs) are an essential component in the tumor microenvironment and have been reported contributes to tumor progression through many mechanisms; however, the detailed mechanism underlying the immune-suppression effect of CAFs is not clearly defined. In this study, human breast cancer-derived cancer-associated fibroblasts were cultured, and CAFs-derived exosomes in culture medium were isolated. Using miRNA profiles assay, we identify a significantly higher level of microRNA-92 in CAFs exosomes isolated. After treatment by CAF-derived exosomes, breast cancer cells express higher PD-L1, accompanied with increased miR-92 expression. Increased PD-L1 expression which induced by CAF- derived exosomes significantly promotes apoptosis and impaired proliferation of T cells. The underlying mechanism of this effect was studied, proliferation and migration of breast cancer cells were increased after transfection of miR-92, LATS2 was recognized as a target gene of miR-92, and further confirmed by luciferase assay. Immunoprecipitation (IP) shown that LATS2 can interact with YAP1, chromatin immunoprecipitation (ChIP) confirmed that after nuclear translocation, YAP1 could bind to the enhancer region of PD-L1 to promotes transcription activity. Furthermore, the animal study confirmed that cancer-associated fibroblasts significantly promotes tumor progression and impaired function of tumor infiltrated immune cells in vivo. Our data revealed a novel mechanism that can induce immune suppression in the tumor microenvironment.